Nanometer-scale siRNA carriers incorporating peptidomimetic oligomers: physical characterization and biological activity - Konca, Yeliz Utku (Dove Medical Press, 2014)
Synthetic short interfering RNA (siRNA) oligonucleotides can trigger the RNA interference pathway and lead to selective gene silencing. Despite considerable enthusiasm and investment, formidable challenges remain that may deter translating this breakthrough discovery into clinical applications. In particular, the development of efficient, nontoxic, nonimmunogenic methods for delivering siRNA in vivo has proven to be exceptionally challenging. Thorough analysis of the relationship between the structure and function of siRNA carrier systems, both in isolation and in complex with RNA, will facilitate the design of efficient nonviral siRNA delivery vehicles. In this study, we explore the relationship between the physicochemical characteristics and the biological activity of “lipitoid” compounds as potent siRNA delivery vehicles. Lipitoids are cationic peptidomimetic oligomers incorporating a peptoid and a phospholipid moiety. Lipitoids can associate with siRNA oligonucleotides and self-assemble into spherical lipitoid-based nanoparticles (LNPs), with dimensions that are dependent upon the medium and the stoichiometric ratio between the cationic monomers of the lipitoid and anionic siRNA oligonucleotides. The morphology, gene silencing efficiency, and cytotoxicity of the siRNA-loaded LNPs are similarly sensitive to the stoichiometry of the complexes. The medium in which the LNPs are formed affects the assembled cargo particles’ characteristics such as particle size, transfection efficiency, and stability. Formation of the LNPs in the biological, serum-free medium OptiMEM resulted in LNPs an order of magnitude larger than LNPs formed in water, and were twice as efficient in siRNA transfection compared to LNPs formed in water. Inhibitor studies were conducted to elucidate the efficiency of lysosomal escape and the uptake mechanism of the siRNA-loaded LNPs. Our results suggest that these lipitoid-based, siRNA-loaded spherical LNPs are internalized through a lipid raft-dependent and dynamin-mediated pathway, circumventing endosomal and lysosomal encapsulation. The lipitoid-siRNA nanospheres proved to be suitable platforms for investigating the critical parameters determining the efficiency of transfection agents, revealing the necessity for conducting characterization studies in biological media. The investigation of the LNP internalization pathway points to an alternative uptake route that bypasses the lysosome, explaining the surprisingly high efficiency of LNPs and suggesting that the uptake mechanism should be probed rather than assumed for the next generation of rationally designed transfection agents.